RoadEye - The Intelligent Transportation System - Ibrahim, Mennatallah (2017)
RoadEye is an intelligent transportation system project that will solve many traffic problems and make traffic safer. RoadEye is a system that will be able to detect weather conditions, maintain a safe distance and fixed speeds between vehicles. The proposed project implements a vehicle-to-vehicle-to-infrastructure system. The current system two features: Platooning for the vehicle-to-vehicle communication and SWIW (Spot-Weather-Impact-Warning) for the vehicle-to-infrastructure communication. The communication between vehicles and infrastructure is set up using different wireless technologies (i.e. XBee firmware, S1 module using the IEEE 802.15.4 and the S2C using ZigBee). RoadEye aims to reduce traffic accidents, it primarily focuses on implementing an intelligent transpotation system in the Gulf region.